2010
DOI: 10.1186/1475-2875-9-377
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting treatment-seeking for febrile illness in a malaria endemic block in Boudh district, Orissa, India: policy implications for malaria control

Abstract: BackgroundOrissa state in eastern India accounts for the highest malaria burden to the nation. However, evidences are limited on its treatment-seeking behaviour in the state. We assessed the treatment-seeking behaviour towards febrile illness in a malaria endemic district in Orissa.MethodsA cross-sectional community-based survey was carried out during the high malaria transmission season of 2006 in Boudh district. Respondents (n = 300) who had fever with chills within two weeks prior to the day of data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 18 publications
7
50
3
Order By: Relevance
“…The level of use of CMDs in our study is within the range of 2–59%, which has been reported in other studies 9,14,21,30. Unlike in our study in which most CMDs were newly enrolled, Ajayi and others enrolled pre-existing CMDs, and this may have resulted in the much higher use rate of CMDs (59%) 14.…”
Section: Discussionsupporting
confidence: 56%
“…The level of use of CMDs in our study is within the range of 2–59%, which has been reported in other studies 9,14,21,30. Unlike in our study in which most CMDs were newly enrolled, Ajayi and others enrolled pre-existing CMDs, and this may have resulted in the much higher use rate of CMDs (59%) 14.…”
Section: Discussionsupporting
confidence: 56%
“…The commonest reason that affected their choices of firstline treatment was cost 30.5% which was followed by belief/culture 28.5. This finding contrasts with report of a similar study in Orissa Disrict, India -where distance (66.9%) was the commonest reason giving by the majority of the mothers [20].…”
Section: Discussioncontrasting
confidence: 95%
“…Hence, further studies are required to determine how prevalent the belief that covert HIV testing may accompany testing for malaria actually is in the many countries with a high prevalence of HIV. A delay of over two days before obtaining medical assessment after symptoms of suspected malaria started was seen in 49% of the study population, and similar delays have been observed from other observational studies from Nigeria [22], Senegal [23], Ethiopia [7,24] and India [19,25]. The estimates that these data provide of the impact of fear of covert HIV testing necessarily do not include those who died before presentation with malaria, and hence may potentially underestimate the overall impact of these beliefs on time to presentation.…”
Section: Discussionsupporting
confidence: 83%